Navigating Christian School Resilience, Lesson Learn from Decline to Survival Strategies - Kui, Daniel Ong Kim; Widjaja, Anton Wachidin; Pramono, Rudy (Journal of Posthumanism, 2025)
This study investigates the decline of Christian private schools in Indonesia from the perspective of Resource-based View, Dynamic Capabilities and Stakeholder Management. The study employed qualitative research design, utilizing in-depth case studies to explore the cause of decline following the guidelines of Qualitative Data Analysis Methods, conducted a systematic and rigorous data analysis involving data reduction, data display, and conclusion verification. We used cycles of coding development to analysis the data and identifying patterns and themes that shed light on the decline of Christian schools. Our data is collected through 17 semi-structured interviews with 22 executives from three Christian school providers that have experienced decline and two association bodies of Christian education, all in five cities in Indonesia. Our findings revealed four major themes as the cause of setbacks, including schools that failed to adapt to changing environment due to lack of human capital resource allocation and neglected stakeholder engagement were more likely to experience decline. However, the study also identified three key propositions that can contribute to the revival of Christian schools, along with the development of schools’ resources in form of Foundation managements’ role and capabilities in form of planning with context-driven, and incorporating stakeholders that build relationship by student-centered approach, all as the integrative perspective for survival strategy. The results have implication for Christian educational Foundation senior management team, school executives and stakeholders seeking to revitalized and sustain educational institution in a rapidly changing environment.